2019
DOI: 10.3389/fimmu.2019.00912
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Mediate Synaptic Material Clearance at the Early Stage of Rats With Retinitis Pigmentosa

Abstract: Resident microglia are the main immune cells in the retina and play a key role in the pathogenesis of retinitis pigmentosa (RP). Many previous studies on the roles of microglia mainly focused on the neurotoxicity or neuroprotection of photoreceptors, while their contributions to synaptic remodeling of neuronal circuits in the retina of early RP remained unclarified. In the present study, we used Royal College of Surgeons (RCS) rats, a classic RP model characterized by progressive microglia activation and synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 62 publications
4
28
0
Order By: Relevance
“…Indeed, numerous engulfment receptors relevant to efferocytosis are known (62). Moreover, increased staining of complement factor C1q has been reported in RCS retina in the OPL where microglia may phagocytose synaptic components (63). The same study found that elimination of retinal microglia by systemic treatment with a CSF1 receptor inhibitor had no effect on photoreceptor light responses (and worsened inner retinal responses), although drug administration via dietary supplementation only started at P15 and may not have been effective immediately in pre-weaning rats.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous engulfment receptors relevant to efferocytosis are known (62). Moreover, increased staining of complement factor C1q has been reported in RCS retina in the OPL where microglia may phagocytose synaptic components (63). The same study found that elimination of retinal microglia by systemic treatment with a CSF1 receptor inhibitor had no effect on photoreceptor light responses (and worsened inner retinal responses), although drug administration via dietary supplementation only started at P15 and may not have been effective immediately in pre-weaning rats.…”
Section: Discussionmentioning
confidence: 99%
“…If these neurons were injected with parasite protein (either with or without subsequent invasion) during early CNS infection, their survival would suggest that not all T. gondii-injected neurons are cleared from the CNS. The lack of clearance over the long-term would imply that these neurons are functional, as non-functional neurons are normally cleared by microglia 65,66 . Alternatively, if parasitic cysts continually rupture, individual parasites may interact with and invade new neurons continually throughout the host's lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Microglial activation is an important hallmark of neuroin ammatory diseases including AMD [14,21,22], as resident immunizing cells in retina, microglia sustain microenvironmental equilibrium and its dysfunction initiates a series of retinal degenerative performance [17,[23][24][25][26]. Therefore, considered that there was no well-established AMD animal models to mimic both the etiological and morphological properties of AMD [27,28], we focused on microglial activation by subretinal injection of Aβ 1-42 in mice and studied its indirect effect on photoreceptors by releasing the in ammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%